Application of Solvent-Casted Gelatin Films for Environmental Remediation and Wastewater Treatment Purposes - Bhardwaj, Nikita; Maitra, Jaya (Chemistry and Biochemistry: Research Progress Vol. 5, 2025)
Gelatin, derived from collagen through partial hydrolysis, is widely recognized for its effectiveness in film formation and diverse applications across various industries. Despite its effectiveness, gelatin films encounter challenges such as poor water solubility and limited adsorption capacity for heavy metals, which restrict their broader application in environmental remediation. This study aims to enhance the practical applications of gelatin films in environmental remediation and contribute to the development of sustainable materials. In the study, gelatin films were prepared by dissolving gelatin in distilled water with mechanical stirring, followed by casting the solution into films. The physico-chemical properties of the films were evaluated. The biodegradability of these films was confirmed through soil burial tests, and their rapid dissolution in water was evident, with a measured water solubility of 29 ± 1.6%. The structural integrity and thermal stability of the films were characterized using UV and FTIR. The films exhibited significant UV-visible light absorbance, with a peak at 300 nm within the 280 to 480 nm range. FTIR spectra revealed the characteristic amide peaks of gelatin, indicating the presence of key functional groups. This research also highlighted the films' ability to adsorb copper ions from acidic solutions, as demonstrated by iodometric titration, and to treat hard water through complexometric titrations. These findings illustrate the potential of gelatin films as effective adsorbents for copper ions and water hardness, making them promising candidates for environmental remediation and wastewater treatment. These characteristics align with green chemistry principles, emphasizing the importance of environmentally friendly technologies in addressing heavy metal pollution. The study highlights rapid water solubility as a critical limitation of gelatin films, restricting their functionality in aqueous and humid environments. Addressing this challenge could significantly enhance their stability and expand their potential applications in environmental remediation and water treatment technologies.